2019
DOI: 10.1111/apt.15222
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world effectiveness and safety of glecaprevir/pibrentasvir for the treatment of chronic hepatitis C infection: data from the German Hepatitis C‐Registry

Abstract: Background: Glecaprevir/pibrentasvir is a pangenotypic direct-acting antiviral regimen approved for treating adults chronically infected with hepatitis C virus (HCV).There are limited real-world data on glecaprevir/pibrentasvir to date.Aim: To evaluate the effectiveness and safety of glecaprevir/pibrentasvir under realworld conditions in the German Hepatitis C-Registry (DHC-R). Methods:The DHC-R is an ongoing, non-interventional, multicentre, prospective, observational cohort study that monitors patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
64
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 11 publications
16
64
1
2
Order By: Relevance
“…Several well-designed, robust clinical trials have demonstrated the safety (147) and high curative efficacy of glecaprevir/pibrentasvir (148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158) and sofosbuvir/ velpatasvir (159)(160)(161)(162)(163)(164) among treatment-naive persons without cirrhosis regardless of HCV genotype. These findings have been confirmed in real-world cohort studies for both glecaprevir/pibrentasvir (165)(166)(167) and sofosbuvir/velpatasvir. (167)(168)(169)(170)(171) Based on these data, 8 weeks of glecaprevir/pibrentasvir or 12 weeks of sofosbuvir/velpatasvir is recommended for adults eligible for the simplified treatment algorithm.…”
Section: Simplified Hcv Treatment Algorithm For Treatment-naive Adultsupporting
confidence: 58%
See 2 more Smart Citations
“…Several well-designed, robust clinical trials have demonstrated the safety (147) and high curative efficacy of glecaprevir/pibrentasvir (148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158) and sofosbuvir/ velpatasvir (159)(160)(161)(162)(163)(164) among treatment-naive persons without cirrhosis regardless of HCV genotype. These findings have been confirmed in real-world cohort studies for both glecaprevir/pibrentasvir (165)(166)(167) and sofosbuvir/velpatasvir. (167)(168)(169)(170)(171) Based on these data, 8 weeks of glecaprevir/pibrentasvir or 12 weeks of sofosbuvir/velpatasvir is recommended for adults eligible for the simplified treatment algorithm.…”
Section: Simplified Hcv Treatment Algorithm For Treatment-naive Adultsupporting
confidence: 58%
“…Eight weeks of the daily fixed‐dose combination of glecaprevir (300 mg)/pibrentasvir (120 mg) gained FDA approval for use in treatment‐naive or interferon‐experienced adolescents aged ≥ 12 years or weighing ≥ 45 kg with any HCV genotype infection, without cirrhosis or with compensated cirrhosis (Child‐Pugh A). Although the registration trial included only adolescents with genotype 1‐4, glecaprevir/pibrentasvir garnered FDA approval for all genotypes based on the safety and efficacy of the regimen demonstrated in adults . The recommendations for use of glecaprevir/pibrentasvir in treatment‐experienced adolescents are also based on clinical trial data from adults .…”
Section: Hcv In the Pediatric Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][32][33][34] Furthermore, 549 (83.4%) of our patients received 8-week treatment regimen, implying that most patients were easy-to-treat population. [18][19][20][21][22][23][24] Although the SVR 12 rate in cirrhotic patients receiving 12-week treatment regimen (94.2%) were numerically lower that the non-cirrhotic patients receiving 8-week treatment (98.9%) by EP analysis, the PP analysis showed that only 2% of the cirrhotic patients had virologic failure. 35 Among the 6 patients receiving 16-week treatment regimen, includ- The causal relationship between the symptoms and the use of GLE/PIB was unclear.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Following the clinical trials which demonstrated the excellent safety and efficacy by GLE/PIB, the real-world data from Western countries and Japan revealed that the SVR 12 rates according to label recommendation were also excellent and were comparable to the reports from clinical trials. [20][21][22][23][24][25][26][27] In 2018, GLE/PIB was reimbursed by Taiwan National Health Insurance (NHI) for patients with chronic HCV infection who had a hepatic fibrosis stage of ≥F3. In 2019, Taiwan NHI cancelled reimbursement restriction and approved physicians to treat all HCV viraemic patients by GLE/PIB.…”
Section: Introductionmentioning
confidence: 99%